WINTER WHEAT PRODUCTIVITY IN DEPENDENCE ON THE METHODS OF PRIMARY TILLAGE IN THE NIZHNEE POVOLZHIE - Yu. N. Pleskachev (Зерновое хозяйство России, 2019)
The result of the study was an establishment of dependence of winter wheat productivity on a method of a primary tillage. There has been identified an advantage of deep chiseling on 0.35–0.37 m over moldboard plowing on 0.20–0.22 m, over disk tillage on 0.12–0.14 m and direct sowing. Plots with deep chiseling showed the best performance compared with other methods of primary tillage in density, porosity, humidity and, consequently, winter wheat productivity.